Percepção da afetividade e das emoções na prática pedagógica de professores de Ciências da Natureza - Gutierrez, João Pedro Fermino (2022)
The present reality defies us to think an education that overcomes the content-focused approach, highly spread in pedagogical practices. The circumstances experienced by COVID-19 pandemic intensified an already urgent situation: the need of restoring the humane dimension of teaching. Providing a humane formation to our students means to integrate affective dimension to the cognitive dimension in pedagogical practice. This study aimed to identify the perception of Natural Sciences teachers (Chemistry, Physics and Biology) on emotions and affectivity in their practices during classes to High School students and how emotions and affectivity were related to and integrated with cognition, having as theoretical support Vygotsky and Wallon ideas. To achieve it, this mastering degree research was qualitative whose methodology consisted in doing individual semi-structured interviews with three teachers. The analysis was made by the Discursive Textual Analysis, with the categorization and discussion of parts of the transcript speeches and reports of the researcher’s observations. As conclusions from the interviewed teachers’ speeches, we realize they have the perception that the affective dimension, theirs and their students’, is part of the development processes which occur in school. They also reflect on the affective dimension and, even though it has not been formalized systematically in courses how to develop it properly, they attempt to integrate it to their work with the cognitive dimension so students’ education can be complete and the teaching-learning processes can be enriched by more accurate pedagogical mediations.